Reinventing Medical education in the COVID-19 era - Das, Saswati (Asian Journal of Medical Sciences, 2021)
Since the beginning of the year 2020, COVID-19 pandemic has engulfed the whole world. Many cities in the world have been under lockdown during this outbreak and the regular classes, clinical, laboratory sessions have been suspended in most medical schools. In the midst of this pandemic, we have had to reinvent the pedagogy of undergraduate medical teaching. The ongoing crisis has motivated medical teachers to come up with a contingency plan for continuing training in the face of adversary. As in-person training had to be avoided, the traditional methods of teaching like didactic lectures, tutorials, case discussions and practical laboratory sessions were of no value in the midst of this pandemic. This led the educationists to explore e-learning resources in order to carry on the medical school training program. There are several challenges in designing a successful e-learning program. Medical institutions must identify sustainable e-learning solutions specially in resource-constrained settings. This perspective article discusses how medical education has been affected by COVID-19 around the world and how it has made educators rethink their teaching strategy. The paradigm shift to e-learning during this outbreak may encourage medical schools to revisit and redesign their curriculum to more versatile programs in future. The experiences gathered during this period might bring about groundbreaking changes in how medicine is taught.